"Ride-sharing", virtual capital and impacts on labor in Cape Town, South Africa. Issue 3 (3rd July 2019) - Carmody, Pádraig; Fortuin, Alicia
ABSTRACT: Informalization and casualization have been twin meta-trends in African development over the last several decades. However these processes are also now being articulated with, and altered by, processes of virtual accumulation and informationalization, giving rise to what some have called Uberization. What does the rise of the 'sharing' economy mean for employment practices and labor relations and conditions in Africa? This paper examines the implications of this phenomenon through a case study of 'ride sharing' operations in Cape Town. It finds hollowing out of the formal sector and the creation of a new (in)formal sector, where drivers are engaged through use of a mobile phone applications, but are still liable for taxes to the state. This has led to the emergence of a new form of 'virtual capital' which extracts 'value' from assets it doesn't own, and labor it doesn't manage.